Radiative, conductive and convective heat-transfers in a single Monte Carlo algorithm. (January 2016) - Fournier, Richard; Blanco, Stéphane; Eymet, Vincent; Hafi, Mouna El; Spiesser, Christophe
Abstract: It was recently shown that null-collision algorithms could lead to grid-free radiative- transfer Monte Carlo algorithms that immediately benefit of computer-graphics tools for an efficient handling of complex geometries [1, 2]. We here explore the idea of extending the approach to heat transfer problems combining radiation, conduction and convection. This is possible as soon as the model can be given the form of a second-kind Fredholm equation. In the following pages, we show that this is quite straightforward at the stationnary limit in the linear case. The oral presentation will provide corresponding simulation examples. Perspectives will then be drawn concerning the extension to non-stationnary cases and non-linear coupling.